Utility of Trabecular Bone Score (TBS) in Bone Quality and Fracture Risk Assessment in Patients on Maintenance Dialysis - Poiana, Catalina; Dusceac, Roxana; Niculescu, Dan Alexandru (Frontiers in Medicine, 2022)
Maintenance dialysis is associated with almost universal changes in bone metabolism collectively known as chronic kidney disease—mineral and bone disorder (CKD-MBD). These are accompanied in various proportions by bone loss and altered bone quality that led to an increased risk of fracture. Osteoporosis, age-related or postmenopausal, a condition that often coexists with CKD, is also a leading cause of fracture. Dual-energy X-ray densitometry (DXA) is the main tool for assessing the bone quantity and bone loss and the associated fracture risk. It has been validated in both CKD-MBD and osteoporosis. Trabecular bone score (TBS) is a DXA-derived algorithm for the evaluation of bone microarchitecture, and its clinical value has been repeatedly demonstrated in large cohorts of osteoporotic patients. However, its utility in patients on maintenance dialysis has not been conclusively shown. Published studies showed a lower TBS score and implicitly an altered bone microarchitecture in patients on maintenance dialysis, even after adjusting for various variables. Moreover, FRAX-based fracture risk is higher after adjusting for TBS, showing promise on an algorithm better estimating the clinical fracture risk in dialysis patients. However, TBS has not been demonstrated to independently predict clinical fractures in prospective studies on dialysis patients. Also, aortic calcifications and altered fluid balance could significantly affect TBS score and could hamper the widespread clinical use in patients on maintenance dialysis. In this mini-review, we focus on the benefits and pitfalls of TBS in the management of CKD-MBD and fracture risk assessment in patients on maintenance dialysis.